Neuroleptic Malignant Syndrome Simulation Case - Jessica Brooks; Britney Anderson; Amy Zosel (Association of American Medical Colleges, 2010)
Abstract This simulation case is designed for emergency medicine residents and for medical students to review the diagnosis, work up, and management of neuroleptic malignant syndrome (NMS). The learners are presented with a critically ill patient, and must elucidate the appropriate history, determine a differential diagnosis, and manage the patient's condition. Debriefing at the end of the case will give the instructor the opportunity to review NMS with the participants. This simulation case has been run on Denver Health Emergency Medicine residents with success. Residents are asked to evaluate a simulation patient with minimal information and come up with a differential diagnosis based on signs and symptoms. The practice of working through a differential diagnosis and the management of this disease process was a valuable learning experience for those involved. Neuroleptic malignant syndrome, and the other febrile toxicological emergencies, are not commonly seen disease processes. This simulation exercise provides a safe learning environment for those involved and enables them to feel more comfortable with the management of these types of patients.